A season for second chances - Bayliss, Jenny (G.P. Putnam's Sons, 2021)
"A charmingly quirky seaside town offers a recently separated restaurateur a fresh start and possibly a new lease on love in A Season for Second Chances, by the author of The Twelve Dates of Christmas"--